Integrating environment into agriculture and forestry : progress and prospects in Eastern Europe and Central Asia - Whitford, Peter; Montanari Stephens, Emanuela (World Bank, 2008)
This study reviews how the integration of environmental concerns into agriculture and forestry is progressing in the countries of Southeastern Europe (SEE) and of Eastern Europe, Caucasus, and Central Asia (EECCA) since 2000 and assesses prospects for the future. The present report is a contribution to the environment for Europe process. At the Fifth Ministerial Conference in Kiev in 2003, participants decided to pay greater attention to the needs of the EECCA and adopted an environmental strategy for the sub-region. The commitments made under that strategy are taken as benchmarks against which progress is assessed, recommendations made, and emerging environmental priorities reviewed. This report also includes an assessment of SEE countries and territories. The analysis provided here is intended primarily to inform discussions during and after the sixth environment for Europe Ministerial Conference, to be held in Belgrade in October 2007. The main text of this report provides a synthesis of major regional issues and trends, with broad recommendations for future directions and priorities. The annexes provide a wealth of data along with detailed country reviews for the 22 countries and territories studied.